Single value devices. (2015) - Mader, Angelika; Dertien, Edwin; Kolkmeier, Jan; Reidsma, Dennis
We live in a world of continuous information overflow, but the quality of information and communication is suffering. Single value devices contribute to the information and communication quality by focussing on one explicit, relevant piece of information. The information is decoupled from a computer and represented in an object, integrating into daily life. The contribution of this paper is on different levels: first, we identify the class of single value devices, and, second, illustrate it by examples in a survey. Third, we collect the characterisations of single value devices in a taxonomy. The taxonomy provides also a collection of design choices allowing to find new combinations or alternatives more easily, and facilitating the design of new, meaningful, effective and working objects. Finally, when we want to step from experimental and conceptual examples to commercialisable products a number of issues become relevant that are identified and discussed in this paper.